Perceptions of knowledge management in Brazilian software development companies - dos Santos, Juliana Oliveira; Martins, Guilherme Augusto dos Reis; de Souza, Érica Ferreira; Felizardo, Katia Romero; Meinerz, Giovani Volnei (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2022: Anais do XXV Congresso Ibero-Americano em Engenharia de Software, 2022)
The software development companies conduct activities that generate a considerable amount of knowledge. Knowledge Management (KM) allows working with the generated knowledge helping in organizational learning. However, professionals in software companies still face several challenges to articulate and leverage knowledge in the organization. We aim at providing evidence about how KM has been adopted in practical environments of software development. We designed a survey instrument that was distributed to Brazilian software development professionals. The survey results improved the current understanding of KM and how it manifests itself in practical software development environments.